Peer Group and Positive Affirmations Affect on Physical Changes and Psychological Consequences of Menopause - Siti Masitoh; Yudhia Fratidhina; Heriza Syam (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Menopause is a woman's last menstrual period influenced by reproductive hormones, occurring in her fifties. Various efforts can be made to overcome the symptoms and complaints in menopausal women, including peer groups and positive affirmations. The purpose of the study was to determine the effect of the peer group model and positive affirmations on physical and psychological changes due to menopause in the work area of ​​the Pondok Rangon Community Health Center, Cipayung District, East Jakarta. This type of research is a quasi-experiment with two group pre-test post-test. The sampling technique used the purposive sampling method with a total sample of 50 respondents. The results showed that the average age of the respondents was 53.36 years, with the majority of respondents (64%) having low education, not working (86%), and most of them being multiparous (70%). The intervention group results showed a significant difference before and after treatment, both in physical changes (p-value 0.001) and psychological (p-value 0.000). The control group found no significant difference in physical changes (p-value 0.085) and psychological changes (p-value 0.174). The study concludes a decrease in physical and psychological changes in the intervention group who received peer group treatment and positive affirmations compared to the control group who did not receive treatment. Menopausal women can use the peer group model and positive affirmations to overcome the complaints of menopausal women.